Investigation of slip flow dynamics involving Al2O3 and Fe3O4 nanoparticles within a horizontal channel embedded with porous media - Mahmmoud M. Syam; Muhammed I. Syam (International Journal of Thermofluids)
This study examines the effects of slip on the two-dimensional flow of nanofluids in a semi-porous channel designed with two long rectangular plates embedded in porous media. One wall of the channel is rigid, and exhibits slip, while the other is porous. A transverse magnetic field of uniform strength was applied in the direction of the flow. The study considered magnetic nanoparticles Fe3O4 and non-magnetic nanoparticles Al2O3 with water and Ethylene glycol as the base fluid. The operational matrix method is employed to solve the ordinary differential equations. Various flow parameters were illustrated through graphs, revealing that the fluid boundary layer thickness decreased as the Reynolds number increased. Additionally, fluid velocity decreased with increasing slip and porosity parameters. The flow field for magnetic nanoparticles was less than that for non-magnetic particles. These results hold considerable practical value for designing and enhancing nanofluid-based systems. Our study analyzes nanofluid flow and heat transfer in a semi-porous channel under a magnetic field, considering thermophoresis, Brownian motion, and Darcy-Forchheimer drag. We explore how parameters like the Hartmann number, porosity, and thermophysical properties impact flow dynamics and heat transfer. This work offers new insights into nanofluid behavior, with practical implications for efficient cooling and fluid transport systems.